(untitled) (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
Hyperlipidemia is the greatest risk factor of coronary heart disease. Currently available anti-hyperlipidemic drugs have been associated with side effects. Herbal treatment for hyperlipidemia has less/no side effects and is relatively cheap and locally available. In the growing burden of atherosclerosis, the present study was designed to evaluate and to compare the anti-hyperlipidemic effect of Caralluma lasiantha extract with Chromium Picolinate on hyperlipidemia induced by Cafeteria-Diet in Wistar albino rats. Hyperlipidemia was induced by giving Cafeteria-Diet for three months, simultaneously Caralluma lasiantha (10, 20, and 40 mg/kg b.w.) & Chromium Picolinate (10 mg/kg b.w.) were administered for each group respectively once every day by oral route throughout the experimental period and serum lipid levels were estimated once every month. There was a marked decrease in total cholesterol (TC), triglycerides (TG), low density lipoprotein (LDL) and very low density lipoprotein (VLDL) levels. Also there was a significant increase in high density lipoprotein (HDL) levels after the treatment with Caralluma lasiantha extract compared to untreated experimental rats and the lipid profile was comparable with Chromium Piclinate treared rats. The present work indicated that Caralluma lasiantha extract significantly suppressed the Cafeteria-Diet induced hyperlipidemia in Wistar albino rats, suggesting the anti-hyperlipidemic activity of the Caralluma lasiantha.